The patient with supine hypertension and orthostatic hypotension: a clinical dilemma. Issue 966 (5th April 2006) - Naschitz, J E; Slobodin, G; Elias, N; Rosner, I
Abstract : Coexistent supine hypertension and orthostatic hypotension (SH-OH) pose a particular therapeutic dilemma, as treatment of one aspect of the condition may worsen the other. Studies of SH-OH are to be found by and large on patients with autonomic nervous disorders as well as patients with chronic arterial hypertension. In medical practice, however, the aetiologies and clinical presentation of the syndrome seem to be more varied. In the most typical cases the diagnosis is straightforward and the responsible mechanism evident. In those patients with mild or non-specific symptoms, the diagnosis is more demanding and the investigation may benefit from results of the tilt test, bedside autonomic tests as well as haemodynamic assessment. Discrete patterns of SH-OH may be recognisable. This review focuses on the management of the patient with coexistent SH-OH.